2000
DOI: 10.1046/j.1523-1755.2000.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

ACEI/ATRA therapy decreases proteinuria by improving glomerular permselectivity in IgA nephritis

Abstract: Our data suggest that ACEI/ATRA therapy may be beneficial in patients with IgAN with renal impairment and nonselective proteinuria, as such patients may respond to therapy with improvement in protein selectivity, decrease in proteinuria, and improvement in renal function. ACEI/ATRA therapy probably modifies pore size distribution by reducing the radius of large unselective pores, causing the shunt pathway to become less pronounced, resulting in less leakage of protein into the urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 26 publications
2
74
0
Order By: Relevance
“…The use of ACEi/ARB was the only intervention associated with a slower rate of renal function decline and prolonged renal survival, in keeping with both published randomized, controlled trials and retrospective reviews demonstrating the renoprotective effect of renin-angiotensin-aldosterone system blockade. 30 -39 These beneficial effects may reflect both hemodynamic and nonhemodynamic antiproteinuric effects of ACEi/ARB 24,35,40 -42 or alterations in glomerular permselectivity 43 ; however, this study was not designed to determine causality or mechanism. Similarly, although MAP was an important determinant of outcome and patients with the highest quartile of MAP had the highest levels of proteinuria, this is not necessarily a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ACEi/ARB was the only intervention associated with a slower rate of renal function decline and prolonged renal survival, in keeping with both published randomized, controlled trials and retrospective reviews demonstrating the renoprotective effect of renin-angiotensin-aldosterone system blockade. 30 -39 These beneficial effects may reflect both hemodynamic and nonhemodynamic antiproteinuric effects of ACEi/ARB 24,35,40 -42 or alterations in glomerular permselectivity 43 ; however, this study was not designed to determine causality or mechanism. Similarly, although MAP was an important determinant of outcome and patients with the highest quartile of MAP had the highest levels of proteinuria, this is not necessarily a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…One strength of this study is that only stable patients were selected and confirmed over a 3-mo run-in phase, which is at variance with most studies on IgAN that enrolled patients shortly after the onset of clinical symptoms and renal biopsy (1,21). Despite these precautions, several patients, who were not as stable as expected, were excluded from entering the follow-up phase.…”
Section: Discussionmentioning
confidence: 99%
“…here are very few randomized, controlled trials (RCT) in IgA nephropathy (IgAN), even though it is the most common glomerular disease worldwide (1)(2)(3). In the past decade, angiotensin-converting enzyme inhibitors (ACE-I) have raised great hopes of successfully treating chronic renal disease; they show beneficial effects not only in controlling hypertension but also in reducing the process of renal sclerosis (4 -5).…”
mentioning
confidence: 99%
“…In addition, electrophoretic patterns of urine proteins have been used to predict outcomes in CKD. A predominantly low molecular weight (LMW) pattern of urinary proteins on sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) predicts progression in IgA nephropathy [44], and changes in protein selectivity may parallel patterns of response to therapy in that disease [45]. The protein selectivity index (SI), which dates back to the 1960s, can be highly predictive of steroid responsiveness in idiopathic nephrotic syndrome [46].…”
Section: Proteinuriamentioning
confidence: 99%